Innovative Methods of teaching Yoga at the Primary Stage - Kumar, Manish; Panwar, Poonam; Gowda, Paran (THE PRIMARY TEACHER, 2017)
It is a widely accepted fact that ‘yoga’ promotes a healthy way of life. Daily practise of yoga helps one to stay physically fit, mentally alert and emotionally balanced, which leads to spiritual development. It is important to introduce yoga at the primary stage of education and make children aware of common yoga terminology at an early age. Therefore, yoga terms must be taught to the young learners in simple and practical manner. This paper is in continuation with the analysis of the ‘ABC of Yoga Chart(s)’, which was carried in the July 2017 issue of the journal. The yoga terms in the chart analysed have been linked with the 26 letters of the English alphabet. To test the statistical efficacy of the chart on primary students, 170 teachers were selected from 12 schools of Kurukshetra in Haryana.